Tinjauan Ekonomi Syariah Terhadap Legalitas Penghasilan Youtuber Di Era Digital - Romi, Muhammad; Harroni, Jum; Mawardi, Mawardi (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2025)
This study aims to analyze the legality of YouTubers' income from the perspective of sharia economics and the maqasid of sharia, and to identify the criteria for the halalness of their income sources. The study focuses on the suitability of content, types of advertisements, and forms of contracts used in collaboration with third parties, as well as their relevance to sharia principles. The research method used is a qualitative method with a descriptive-analytical approach. Data were collected through a literature review of fatwas from the Indonesian Ulema Council (MUI), muamalah fiqh literature, and previous research related to the YouTuber profession, sharia economic contracts, and the principles of maqasid of sharia. The analysis was conducted by examining the conformity of YouTubers' income practices with the principles of halal, thayyib, and maslahah, and assessing the implementation of contracts such as syirkah and ju'alah based on sharia provisions. The results of the study indicate that YouTubers' income can be categorized as halal if the content and advertisements broadcast are in accordance with sharia principles, and the cooperation contract fulfills the pillars and requirements of validity, free from elements of usury, gharar, and maysir. From a maqasid sharia perspective, such income must support the goals of preserving religion (hifzh al-din), preserving wealth (hifzh al-mal), and preserving reason (hifzh al-‘aql). MUI Fatwa No. 24 of 2017 serves as the primary guideline for ensuring that YouTubers' digital activities are compliant with sharia, enabling this profession to provide broad benefits, strengthen moral values, and maintain Islamic integrity in the digital age.